(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bubble deck slab was a new floor system of reinforced concrete which contains spherical hollows as concrete economy elements. It is a revolutionary technique which practically eliminates all concrete from the middle portion of a floor slab. The structural dead weight was condensed due to the non-performance of any structural function by the middle part of the slab. High concentration polypropylene spherical balls replace with the in-effective concrete in the center of the slab. Voids in the middle of the slab provide thermal insulation and also leads to 30 to 50 lighter slab. Bubble deck slab allows larger spans between columns supports. In the bubble deck technology reduce the concrete volume by replacing the spherical bubbles, these are locally accessible which was called as PEPSI balls, these balls are made up of HDPE (High Density polyethylene). In this experimental program conventional slab and bubble deck slab are cast with various bubbles arrangement which is continuous arrangement of bubbles within whole slab and two types of another bubbles arrangement in the slab.